(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
Technology no doubt is the engine that drives the modern world, both for destruction and good; and one of the wonders of modern technology is the computer and the allied internet. Modern communication network now relies on the internet using the computer and mobile telephones. In fact, there is no place to hide with the internet and the handy smart phones with which calls are made and pictures and videos recorded and transmitted across boundaries and continents. The advancements in the computer and internet systems in the last decade of the 20th century produced radical changes in both internet connectivity and features available to users through which people are linked across the globe. The three most basic of these internet features that have radically shaped modern communication are, Facebook, Twitters, and the U-Tube, among others. The three are the most popular and core elements of the social media compartment of our modern internet system. Computer technology has broken the boundaries of closed societies and systems, making actions and activities in such systems open and available to the wider world. Through the internet and its core elements, repressive regimes have been exposed and activities going on in liberal societies are shared. Interestingly, Africa became the starting point for the agitation for political change, which was bolstered by the social media. The so-called “Arab Spring”, which first started in Africa through expositions of social media, saw the dismantling of three despotic and ruthless regimes in Arab North Africa, thus giving vent to agitations for an end to dictatorship and illiberality in other Arab states. The paper will examine the role of the social media in political transformation and change of dictatorial regimes in Africa and the consequences such would have on the overall political template of Africa.